2019
DOI: 10.1212/wnl.0000000000008168
|View full text |Cite
|
Sign up to set email alerts
|

Vamorolone trial in Duchenne muscular dystrophy shows dose-related improvement of muscle function

Abstract: ObjectiveTo study vamorolone, a first-in-class steroidal anti-inflammatory drug, in Duchenne muscular dystrophy (DMD). MethodsAn open-label, multiple-ascending-dose study of vamorolone was conducted in 48 boys with DMD (age 4-<7 years, steroid-naive). Dose levels were 0.25, 0.75, 2.0, and 6.0 mg/kg/d in an oral suspension formulation (12 boys per dose level; one-third to 10 times the glucocorticoid dose in DMD). The primary goal was to define optimal doses of vamorolone. The primary outcome for clinical effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 31 publications
1
66
0
1
Order By: Relevance
“…17 First-in-patient phase 2a clinical trials included a 2-week open-label multipleascending-dose (0.25, 0.75, 2, and 6 mg/kg/day) study in 48 DMD boys (4 to <7 years old, steroid naive; VBP15-002) 16 and a subsequent 24-week extension phase (VBP15-003) at the same doses. 18 The phase 2a studies demonstrated that vamorolone was safe at all doses tested, with decreased steroid-associated safety concerns predicted by biomarker studies. Both doseresponsive improvements in clinical outcomes (eg, time to stand from supine velocity and 6-minute walk test, etc.)…”
Section: Vamorolonementioning
confidence: 97%
See 2 more Smart Citations
“…17 First-in-patient phase 2a clinical trials included a 2-week open-label multipleascending-dose (0.25, 0.75, 2, and 6 mg/kg/day) study in 48 DMD boys (4 to <7 years old, steroid naive; VBP15-002) 16 and a subsequent 24-week extension phase (VBP15-003) at the same doses. 18 The phase 2a studies demonstrated that vamorolone was safe at all doses tested, with decreased steroid-associated safety concerns predicted by biomarker studies. Both doseresponsive improvements in clinical outcomes (eg, time to stand from supine velocity and 6-minute walk test, etc.)…”
Section: Vamorolonementioning
confidence: 97%
“…and decreases in proinflammatory corticosteroidresponsive biomarkers were observed. 16,18 The US Food and Drug Administration (FDA) has a guidance regarding the importance of exploring exposure-response relationships in drug development (https://www.fda.gov/media/71277/download). Although PK provides key data to link drug dosing to blood concentrations, in their guidance the FDA notes, "Far less attention has been paid to establishing the relationship between blood concentrations and pharmacodynamic (PD) responses and possible differences among population subsets in these concentrationresponse (often called PK/PD) relationships."…”
Section: Vamorolonementioning
confidence: 99%
See 1 more Smart Citation
“…These were then used to test the anti‐inflammatory effects of a new drug, vamorolone, in Duchenne muscular dystrophy . Initial dose‐ranging pediatric trials in Duchenne muscular dystrophy studied a 24‐fold dose range (0.25– 6.0 mg/kg/day), in which the serum pharmacodynamics biomarkers helped to establish the likely efficacious doses with only a 2‐week exposure study …”
Section: Use Of Biomarkers As Pd End Pointsmentioning
confidence: 99%
“…36 Initial dose-ranging pediatric trials in Duchenne muscular dystrophy studied a 24-fold dose range (0.25-6.0 mg/kg/day), in which the serum pharmacodynamics biomarkers helped to establish the likely efficacious doses with only a 2-week exposure study. 36,37 Clinical end points, as the primary outcome for determining PD in children, can be problematic when end points in pediatric trials differ from those measured in adult trials; use of different outcome measures has been found to be a risk factor for trial failure in children. 28 PD biomarkers show that a biological response has occurred in an individual who has been exposed to a medical product or an environmental agent.…”
Section: Use Of Biomarkers As Pd End Pointsmentioning
confidence: 99%